Historicising the Birangona: Interrogating the Politics of Commemorating the Wartime Rape of 1971 in the Context of the 50th Anniversary of Bangladesh. Issue 6 (2nd November 2021) - Mookherjee, Nayanika
Abstract: Two decades ago, '1971' was deemed to not have a market within Indian publishing houses and media outlets. Yet, one is struck by the contemporary Indian focus on the iconic figure of the Birangona – brave women, a title given by the State of Bangladesh to women raped by the Pakistani army and their Bengali and non-Bengali collaborators during the Bangladesh war of 1971. It is important to engage with the public memory of wartime sexual violence of 1971 beyond the horrific constructions of the Birangona and the potential for propaganda and geopolitical calculations that the narrative engenders for India.